Grau de regressão tumoral avaliado pela ressonância magnética e pela histopatologia após terapia neoadjuvante em pacientes com adenocarcinoma de reto - Fábio Henrique de Oliveira (2016)
Rectal cancer (RC) is a tumor commonly diagnosed in developing countries, accounting for considerable rates of morbi-mortality. The neoadjuvant terapy (TN) with radiotherapy and chemotherapyhas a leading role in the management of this neoplasm, regarding to oncological results and the preservation of anal function. Magnetic resonance imaging (MRI) is one of the main tools for the evaluationof TN results in rectal cancer in order to manage the therapy. OBJECTIVES: To compare the results of the MRI performed straight after TN with histopathologic findings of surgical specimens in patients with CR, underwent radical surgery. METHOD: This is a retrospective study of 31 patients with extraperitoneal RC underwent radical surgery with total mesorectal excision (ETM) with sphincter preservation after performing neadjuvante therapy (TN) with radiotherapy and chemotherapy. The selected patients underwent MRI pelvis with emphasis on rectum, before and after performing TN. The initial stage of the disease was obtained for the first MR, and the second MR (post-TN) was responsible for determination of tumor regression grade (TRG) and downstaging disease. This TRG was compared with the estimated regression obtained by histopathology of the specimen based on Dworak-TRG classification and TNM classification, trying to analyze the degreeof agreement of the two methods and the occurrence of downstaging. RESULTS: Most patients presented downstaging (74,4%) disease after TN when compared to the initial stage. Six patients (19.4%) achieved a complete pathological response. MRI had a sensitivity of 83.3% and specificity of 73.7%, with PPV = 66.7%, NPV = 87.5% and an accuracy of 0.774 in estimating the TRG compared to histopathology. There was no correlation between patient characteristics and pathological findings and the results of TRG. CONCLUSIONS: MRI of the pelvis with emphasis on rectum has good accuracy in the evaluation of patients with RC submitted to TN with radiotherapy and quimioterapy compared with histopathology and should be used routinely in clinical practice.